Pengajaran Al-Quran Braille: Isu Dan Cabaran Semasa - Norakyairee Mohd. Raus; Mohd Nur Adzam Rasdi; Norazman Alias; Norhasnira Ibrahim; Norullisza Khosim; Noornajihan Ja‘afar; Ab. Halim Tamuri; Norshidah Mohamed Salleh; Hajarul Bahti Zakaria (Centreof Quranic Research (CQR), University of Malaya, 2024)
International Journal on Quranic Research (IJQR) Vol.3, No. 4, June 2013, Pp. 79-94